Frequency and Clinical Features of Dengue Infection in a Schoolchildren Cohort from Medellin, Colombia - Berta Nelly Restrepo; Leidy Diana Piedrahita; Ivony Yireth Agudelo; Gabriel Parra-Henao; Jorge E. Osorio (Journal of Tropical Medicine)
To determine the incidence of dengue infection, we established active surveillance of febrile episodes in a cohort of schoolchildren from three schools in Medellin, Colombia. We followed a cohort of 2,379 schoolchildren in 2010 and followed 1,840 of these children the following year. During the follow-up time, 264 schoolchildren displayed 297 febrile episodes; of these, 23 episodes (7.7%) were caused by acute dengue infection. All four dengue serotypes were found, and all of the cases were mild. The most common symptoms in the dengue cases compared with those in other febrile illness were asthenia (96% versus 87%), anorexia (78% versus 57%), rhinorrhea (65.2% versus 58%), abdominal pain (56.5% versus 47.8%), arthralgia (43% versus 33%), and positive tourniquet test (13% versus 3%). This difference was not statistically significant. Pulse was elevated, and systolic arterial pressure was lower in dengue cases compared with other febrile illness (P<0.05). Mosquito indexes were determined in 8 children’s houses and in the schools. Aedes aegypti adults were found in both households and in schools, whereas Aedes aegypti larvae were found only in schools. These results showed an elevated dengue frequency in children, with symptoms similar to those of other febrile illness and transmission risk in households and schools.